Godność dziecka – odkrywana, zdobywana, niszczona - Smolińska- Theiss, Barbara (Horyzonty Wychowania, 2017)
Dignity – engraved in every man’s nature – demands affirmationall the stronger the more person is threatened in his basicand inalienable rights. This threat makes itself felt in particularperiods of human life, it certainly refers to childhood. Child’sdignity was „discovered” at a relatively late stage of developmentof Western societies. At the same time, the history of the pastone hundred years can be deciphered as the time of trampling onchild’s dignity as a result of the dominance of totalitarian systems.Both fundamental sources of threat to child’s dignity lie in thesphere of social communication, where because of the massmedia child is reduced to the consumer of impressions, which iswhy his natural world becomes impoverished. Similarly, in socio-economic dimension childhood is threatened due to the progressof marginalisation processes affecting more and morePolish families.The text constitutes a starting point for pedagogical surveyorientated around the concept of child’s dignity. In this sense, itemerges either as an epistemological category, whose applicationwill allow for clarification and description of the peculiarcharacter of childhood, or as an object of axiological reflectionconsidering man’s relations with transcendental reality.